Cancer incidence and all-cause mortality among civilian men and women employed by the Royal Norwegian Navy between 1950 and 2005. (December 2018) - Strand, Leif Aage; Martinsen, Jan Ivar; Rudvin, Inger; Fadum, Elin Anita; Borud, Einar Kristian
Highlights: Excess breast cancer was seen in the overall male cohort. Male workshop workers showed excess stomach cancer. All-cause mortality in men was lowered. In the overall female cohort, excesses of cancer overall, lung and ovary were found. Female cleaners showed elevated risk of bladder cancer. Abstract: Objective: We aimed to investigate cancer incidence and all-cause mortality in a cohort of 8358 civilians (5134 men and 3224 women) employed by the Royal Norwegian Navy at any time between 1950 and 2005. Methods: The cohort was followed for cancer incidence and all-cause mortality from 1960 through 2015. Standardised incidence ratios (SIR) and mortality ratios (SMR) were calculated from national rates. Separate SIRs were calculated for a subgroup of male workshop workers and another of female cleaners. Results: Overall cancer incidence among men was similar to the reference rate; male breast cancer was more frequent (SIR = 3.23). Male workshop workers showed a SIR of 1.77 for stomach cancer, while their incidence of lympho-haematopoietic cancers was half that of the reference rates. Women had increased risks of overall cancer (SIR = 1.11), lung cancer (SIR = 1.35), and ovarian cancer (SIR = 1.39). Female cleaners showed a SIR of 2.33 for bladder cancer and a lowered incidence of brain cancer (SIR = 0.18). In the overall cohort, all-cause mortality was lower than expected for men (SMR = 0.92) and closer to the reference rate for women (SMR = 0.95). Conclusion: In men, we observed a lowered all-cause mortality and an excess of stomach cancer in workshop workers. In women, increased risks of overall cancer, lung cancer and ovarian cancer was seen. An increased risk of bladder cancer and a lowered incidence of brain cancer was observed among female cleaners.